#TITLE_ALTERNATIVE# - PONTHY , CRESNA
The development of manufacture industry in Indonesia tends to increase to very good direction year by year. These developments become one reason for every company to start to improve their productivity level in order to keep good relationship with its customer. A company likes PT. X faced several problems in fulfill customer's demand. These problems occurred when total demand each month cannot be process because maximum time to produce the products only 720 hours per-month, while company has to deal with 20 different type of products. The main purposes in this research are to identify the main problem in production schedule process, determine the right products to produce in particular month, and determine Master Production Schedule in order to achieve company's objectives. In this matter the solution has to consider company's objective to gain maximum revenue through choosing the right products to produce each month. There are several models in order to processing the data, first is forecasting, second is Aggregate Planning using Integer Linear Programming (ILP), and scheduling. In forecasting, all four methods must be calculate in order to find which method result the lowest mean square error and for the method who resulted the lowest mean square must be chosen as the best method to forecast future demand. Then the result from forecasting will be use to determine the right products to produce in purpose to achieve maximum revenue each particular month. Then the calculations resulted 6-7 products needed to be produce each month and average revenue is Rp 3.912.347.306 each month. By implement this recommendation,company X could maximize its production time in whole month but still far to maximize its capacicty. The conclucion in this research are company X Main problem is limited production time, Linear Cycle Method becomes the best model to calculate future demand, Company X needs to determine the right products to produce in particular month, and SPT becomes the most appropriate scheduling approach base on mean flow time calculation